ECER shows Pahang The Way In Biotechnology - The Star (2008)
The East Coast Economic Region (ECER) master plan has drawn a clear blueprint on the development of biotechnology and biodiversity for Pahang said State Science Innovation Information and Information Technology Committee chairman Datuk Mohd Sharkar Shamsuddin.